The Changing Nature of the Adult Education Professorate: New Roles and Responsibilities in the 21st Century - Elice E. Rogers; Jonathan E. Messemer (Adult Education Research Conference, 2008)
The purpose of this session is to discuss how the roles and responsibilities of the adult education professor have changed in the last 30 years and how the level of power has shifted amidst such change. An examination regarding the changing nature of faculty roles and responsibilities is important because faculty are now challenged in colleges and universities to operate under *market driven models (Kotler & Fox, 1995). In many institutions, faculty are micro-managed to become “organization” men and women, which greatly alters the teaching and learning contract we have with students; resulting in adult education faculty operating as brokers among constituencies for power, influence, and control. Politics and positionality readily becomes a part of this new market driven relationship or model (Cervero & Wilson and Associates, 2001; Johnson-Bailey, 2001; Kotler & Fox, 1995).